The Strategic Role of the Daar Al Uluum Asahan Islamic Institute in Forming a Generation of Superior Muslims - Surono Zamroni; Nilasari Siagian; Andri Nurwandri (Universitas Islam Negeri Sumatera Utara, 2026)
Islamic Higher Education Institutions Daar Al Uluum Asahan Islamic Institute play a pivotal role in shaping an excellent Muslim generation, particularly in Asahan Regency. This study aims to examine the existence and contributions of Daar Al Uluum Asahan Islamic Institute in fostering students’ character, intellectual capacity, and Islamic social competence. Employing a descriptive qualitative approach, data were collected through interviews, observations, and document studies involving community leaders, academics, and Daar Al Uluum Asahan Islamic Institute students. The findings indicate that Daar Al Uluum Asahan Islamic Institute contributes to expanding access to education grounded in Islamic values, strengthening students’ morality, and encouraging their engagement in social and da’wah activities. An integrated curriculum and Islamic campus activities further shape students’ religious identity and competitiveness. Nevertheless, several challenges persist, including limited infrastructure, digital innovation, and inter-institutional collaboration. This study concludes that Daar Al Uluum Asahan Islamic Institute plays a significant role in nurturing an excellent Muslim generation in the region; however, strategic reinforcement, partnerships, and policy support are required to enhance its future contributions